Membangun Keluarga Sukinah melalui Edukasi Kesehatan Reproduksi Keluarga di Desa Nyuhtebel Kabupaten Karangasem - Widnyana, I Made Adi; Kartika, Luh Gede Surya; Dewi PF, Kadek Aria Prima; Arini, Ni Wayan (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
The sukinah family is indicated by good family health. An understanding of the reproductive health of all family members, especially adolescents and children, is one of the important things in creating a happy and prosperous family. This was the background for reproductive health counseling activities in Nyuhtebel Village, Manggis District, Karangasem Regency. The participants of this activity were the representatives of each father in Nyuhtebel Village. It was hoped that the mothers participating in the activity would be able to provide early understanding to children about the dangers of free sex and the importance of maintaining reproductive health. The activity took place on July 18, 2022, at the Nyuhtebel Village Office with dr. I Made Purnama Adimerta, SpOG.subsp FER as the Informan. The result of this activity was that participants understand the impact of early sexual intercourse by children and adolescents and how to maintain the reproductive health of all family members, especially women.